Influence of social support on cognitive change and mortality in old age: results from the prospective multicentre cohort study AgeCoDe - Eisele, Marion; Weyerer, Siegfried (BMC geriatrics, 2012)
Background: Social support has been suggested to positively influence cognition and mortality in old age. However, this suggestion has been questioned due to inconsistent operationalisations of social support among studies and the small number of longitudinal studies available. This study aims to investigate the influence of perceived social support, understood as the emotional component of social support, on cognition and mortality in old age as part of a prospective longitudinal multicentre study in Germany. Methods: A national subsample of 2,367 primary care patients was assessed twice over an observation period of 18 months regarding the influence of social support on cognitive function and mortality. Perceived social support was assessed using the 14-item version of the FSozU, which is a standardised and validated questionnaire of social support. Cognition was tested by the neuropsychological test battery of the Structured Interview for the Diagnosis of Dementia (SIDAM). The influence of perceived support on cognitive change was analysed by multivariate ANCOVA; mortality was analysed by multivariate logistic and cox regression. Results: Sample cognitive change (N = 1,869): Mean age was 82.4 years (SD 3.3) at the beginning of the observation period, 65.9% were female, mean cognition was 49 (SD 4.4) in the SIDAM. Over the observation period cognitive function declined in 47.2% by a mean of 3.4 points. Sample mortality (N = 2,367): Mean age was 82.5 years (SD 3.4), 65.7% were female and 185 patients died during the observation period. Perceived social support showed no longitudinal association with cognitive change (F = 2.235; p = 0.135) and mortality (p = 0.332; CI 0.829-1.743). Conclusions: Perceived social support did not influence cognition and mortality over an 18 months observation period. However, previous studies using different operationalisations of social support and longer observation periods indicate that such an influence may exist. This influence is rather small and the result of complex interaction mechanisms between different components of social support; the emotional component seems to have no or only a limited effect. Further research is needed to describe the complex interactions between components of social support. Longer observation periods are necessary and standardised operationalisations of social support should be applied.